EXPLOITATION OF ORGANIC ULTRAFILTRATION MEMBRANES IN THE REMOVAL OF PEPTONE FROM WASTEWATER - LAURENȚIU TATARU; VALENTIN NEDEFF; EMILIAN MOȘNEGUȚU; MIRELA PANAINTE-LEHADUȘ; DANA ALEXANDRA CHIȚIMUȘ (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In the present paper an ultrafiltration experiment was carried out for testing the polyacrylonitrile (PAN) membrane in the process of peptone separation from wastewater. The evaluation of the applied ultrafiltration process consisted in the monitoring and the recording of the parameters as well as of some indicators that will reveal the PAN membrane efficiency (the percentage of peptone retention on the membrane surface, the volume and quality of the resulting permeate in the pre-established time period). The obtained results showed that the peptone retention efficiency was noticeably, around 20 % and the obtained permeate volume did not decrease greatly, only by 2.5 L over 300 minutes experiment.